Pengaruh Akuntabilitas dan Fairness Terhadap Kinerja Keuangan PT. L-Hijrah Tour & Travel Medan - Manna Wassalwa; Fauzi Arif Lubis; Aqwa Naser Daulay (Jurnal Akuntan Publik, 2023)
This research aims to analyze the influence of accountability and fairness on the financial performance of PT. L-Hijrah Tour & Travel Medan. This research uses primary data by distributing questionnaires as a research source and secondary data in the form of financial reports of PT. L-Hijrah Tour & Travel Medan from 2018-2022. The respondents in this research were employees of PT. L-Hijrah Tour & Travel Medan with 30 responses. The sampling method used in this research is saturated sampling, while the data analysis method is carried out using the multiple linear regression method supported by the SPSS version 22 program. The results of this research show that accountability has a smaller and significant effect, 0.05 (0.002 < 0.05), meaning that in this study Ho was rejected and Ha was accepted. Accountability influences the financial performance of PT. L-Hijrah Tour & Travel Medan.